Dynamics of infection of domestic dogs with parasites in Perm under modern conditions - V. A. Ivanov; T. N. Sivkova (Российский паразитологический журнал, 2025)
The purpose of the research is a comparative analysis of the dynamics of helminth and protozoan infections in domestic dogs in Perm for 2020 to 2023.Materials and methods. The study was conducted at the Department of Infectious Diseases of the Faculty of Veterinary Medicine and Zootechnology of the Perm State Agro-Technological University. The material for the study was 1,439 fecal samples and 2,141 whole blood samples from domestic dogs admitted to private veterinary clinics in Perm. Feces were collected three times to containers with the Turdyev preservative and examined using the combined Kotelnikov-Khrenov method and sequential washing. Venous blood was collected to test tubes with EDTA K3 and analyzed for microfilaria using the V. Yastreb method. The results underwent common statistical processing.Results and discussion. The infection prevalence (IP) in dogs increased slightly from 18 to 20% in 2020–2023 but remained relatively stable as compared to 2015–2019. When studying seasonality, two infection peaks were observed, in spring (March-April) and autumn (September and November). The following helminths and protozoa with direct development cycles occupied the leading place among intestinal parasites: Giardia duodenalis, 2.43% (35); Toxocara canis, 3.33% (48); Cystoisospora spp., 3.13% (45); C. canis, 1.81% (26); and sarcosporidia Sarcocystis sp., 2.02% (29). Microfilaria infection rate in dogs was 1.5% in 2022–2023 without pronounced seasonality. In general, the situation on parasitic diseases in dogs has remained tense in Perm over the past three years.